Introduction to the “Corporate Objective Revisited” Exchange - Walsh, James P. (Organization Science, 2004)
Corporate scandals and abuses of various kinds grab the headlines. Reform initiatives quickly follow outrage. The goal is to constrain our firms' ability to destroy value and lives, while at the same time enabling them to produce and deliver high-quality and profitable goods and services in a very competitive global marketplace. Less obvious but no less important, civil society is increasingly asking corporations to invest directly in social life. Regardless of their productive capabilities, firms can field requests to invest in education, health care, infrastructure, and the like. Sometimes the two ambitions seem to be quite compatible, while at other times they seem to be at odds. Leading a business that is at once socially responsive and economically competitive is a daunting managerial challenge. The theoretical challenge posed by these sometimes competing and sometimes complementary demands is no less daunting. Since the rise of the first corporations two thousand years ago, we have been trying to develop a theory of the firm that explains and guides firm behavior. Sundaram and Inkpen enter this complex and charged world to make a case for a theory of the firm grounded in the pursuit of shareholder wealth. Freeman, Wicks, and Parmar will not let their view go unchallenged. They offer a spirited reply. The exchange embodies everything our Crossroads section can be. We are proud to provide a home for this very thoughtful exchange. This is arguably the most important theoretical and practical issue confronting us today. While we gave Sundaram and Inkpen the last word, we know that the debate is far from over. Indeed, we invite others to think hard about these issues and develop their own point of view. The stakes are enormous.